The Effect of Leadership Style and Compensation on Teacher Performance Moderated by Organizational Culture at the Aresha Indonesia Center Foundation - Diyah Kusumastuti; Priyastiwi Priyastiwi (Majapahit Journal of Islamic Finance and Management, 2025)
This study is motivated by the importance of improving teacher performance as a key factor in achieving educational goals, where leadership style, compensation, and organizational culture are assumed to play significant roles. The purpose of this research is to analyze the influence of leadership style and compensation on teacher performance and to examine the role of organizational culture as a moderating variable at the Aresha Indonesia Center Foundation. The study employed a quantitative approach with a survey method involving 40 teachers as the sample, using a Likert-scale questionnaire, and the data were analyzed through Structural Equation Modeling (SEM) with Partial Least Squares (PLS) using SmartPLS. The findings indicate that both leadership style and compensation have a positive and significant effect on teacher performance. Furthermore, organizational culture was found to moderate the effect of leadership style on performance, but did not moderate the effect of compensation. The synthesis highlights that teacher performance can be improved through strengthening visionary, motivational, and supportive leadership, optimizing fair and relevant compensation systems, and fostering a conducive organizational culture. The policy implications suggest the need for leadership development programs, periodic evaluation of compensation policies, and alignment of reward systems with organizational values ​​to create a harmonious and productive work environment that supports the achievement of educational objectives.